Corrosion and wear study of medium entropy Pb-Sn-Cu alloy for coating application - Gokul M. Pillai; Kuldeep Singh; Shanmugasundaram Thangaraju; Shashinath Jha; Vinod Kumar (Journal of Alloys and Metallurgical Systems)
This study focuses on developing a low-friction coating material using ternary medium entropy alloy using lead (Pb), tin (Sn), and copper (Cu). A Vajra Lep made of Pb-Sn-Cu system reported in Varah Mihir's Jyotish Granth ''Brihat-Samhita'' inspired this research. The reported alloy in the present study was fabricated via the open induction casting method. The microstructure and phase analysis were conducted using a scanning electron microscope and X-ray diffraction. It revealed that Pb-Sn, Pb-rich, and Cu-Sn stable phases are formed during open induction melting-casting. The average microhardness was measured to be 25.3 ± 13.61 HV, suitable for the coating material. The corrosion tests were performed in 3.5 wt% NaCl medium, which showed the formation of a stable passivation layer. Icorr was determined to be 5.63 × 10−7 A/cm2, confirming that the material has high corrosion resistance compared to SS316. The wear tests were carried out at different temperatures with a constant load of 10 N and sliding velocity of 314 mm/s. The wear rate was noted to be 5.623 × 10−5 mm3/Nm at room temperature and decreased to 2.811 x 10−5 mm3/Nm at 80 ℃, exhibiting comparable wear resistance with that of Babbitt alloys. Hence, the study is meaningful in designing the Pb-Sn-Cu based multicomponent alloy system as a coating material for various applications.